Ethnomedical uses of Cananga odorata (Lam.) Hook. f. and Thomson in indigenous traditional medicine among Indonesia ethnic groups - Nuning Rahmawati, Ika Yanti M Sholikhah, Rohmat Mujahid, Yuli Widiyastuti, Agung Endro Nugroho, Abdul Rohman (Journal of Applied Pharmaceutical Science, 2024)
Cananga odorata, commonly known as ylang-ylang, is an evergreen perennial tropical tree belonging to the Annonaceae family, which is traditionally and scientifically reported to have various pharmacological activities. This indigenous medicine study was carried out to document the traditional usage of C. odorata for medicinal reasons by Indonesian ethnic groups. This is one of numerous initiatives aimed at preserving indigenous knowledge and medical practices maintained by the community. Data were acquired during 2015 and 2017 through in-depth interviews with selected traditional healers from each ethnic group throughout 34 Indonesian provinces, who were chosen using a purposive sampling approach based on inclusion criteria. The information gathered includes the demographic data of healers, medicinal plants used, potions, and their applications for health purposes. Following the completion of the interview with the informant, specimens of medicinal plants were collected. Data quantification was accomplished by examining the value of plant parts and doing a simple ranking analysis for multihealth purposes. This study revealed 42 traditional applications of C. odorata by 36 traditional healers from 28 ethnic groups in 16 provinces to overcome 18 diseases. Cananga odorata was primarily obtained from the woodland instead of the house garden and other environments. Skin disease was identified as the most prevalent indication of C. odorata, in agreement with the most commonly employed administration method, the external route. Leaves became the foremost prominent plant part utilized by healers. This study emphasized the significant role of traditional healers in healing various illnesses with C. odorata and the variations in C. odorata ethnomedical usage as a traditional remedy in Indonesia. Nonetheless, cultivating initiatives should be started as more than 60% of identified C. odorata has yet to be grown. The study’s findings are likely to benefit various stakeholders, serve as baseline data for further studies on the efficacy and safety of C. odorata, and contribute to efforts for developing health products that employ C. odorata.
Keywords: Cananga odorata, Annonaceae, traditional healer, ethnopharmacology, cultivation effort